Penguatan Kelembagaan Smart Farmer’s Group (Sfg) Dalam Rangka Pengembangan Kakao Di Desa Jambewangi - Fauziyah, Diana; Raharto, Sugeng; Wibowo, Yuli (Abdi Panca Marga, 2022)
Poktan Manggar Kencono Jambwangi is a farmer group whose purpose formation is to facilitate the activities carried out by cocoa farmers in the village of Jambwangi. The farmer group was formed by and for farmers, so that the focus of the development was to farmers themselves. Therefore, it is very necessary to strengthen and empower the farmer group towards the independent farmer group (Farmer's Group Autonomy) based on superior HR capabilities (Smart Farmer's Group \/ SFP). The method made in this service is in the form of counseling, discussions and assistance about the preparation of organizational structures, job descriptions, and standard operating procedures for later farmer groups to be able to manage their organizations effectively and efficiently because supported by superior peasant human resources capabilities. The results of the Poktan Manggar Kencono Jambevantan dedication still require coaching and assistance in the administration of good and correct organizational, organizational structures and also the application of a clear job description \/ division of tasks between existing parts of the organizational structure and operational standards procedures. This service is important to provide understanding that the preparation of the organizational structure, job description, and standard operating procedure based on the needs of farmer groups so that the farmer's melompo in running its business can be more effective and efficient Keywords: SFG, Organizational structure, Job description, SOP,